The Spatiotemporal Variability of Cloud Radiative Effects on the Greenland Ice Sheet Surface Mass Balance. Issue 12 (18th June 2020) - Izeboud, M.; Lhermitte, S.; Van Tricht, K.; Lenaerts, J. T. M.; Van Lipzig, N. P. M.; Wever, N.
Abstract: To better understand and quantify the impact of clouds on the Greenland Ice Sheet surface mass balance (SMB), we study the spatiotemporal variability of the cloud radiative effect (CRE). The total CRE is separated in short‐term and long‐term impacts by performing multiple simulations with the SNOWPACK model for 2001‐+2010. The annual total CRE is 16.8 ± 4.5 W m −2, reducing the SMB with −157 ± 3.8 Gt yr −1 . Summer cloud radiative cooling is −6.4 ± 5.7 W m −2 in the ablation area, increasing the SMB with 121 ± 2.2 Gt yr −1 . The annual integrated impact is cloud‐reduced SMB of −36 Gt yr −1 . The short‐term effect dominates the opposing long‐term effects through the albedo‐melt feedback. A long‐term warming effect decreases the albedo and so preconditions the surface for enhanced (summer) melt. The impact of the CRE, determined by spatial, temporal and initial conditions, explains existing conflicted views on the role of cloud radiation and emphasizes the need for accurate cloud and albedo representations in future studies. Key Points: Total cloud radiative warming occurs year‐round, except in the ablation area during summer When cloud radiative cooling occurs, clouds reduce mass loss and dominate the impact on the surface Short‐term and long‐term cloud effects are opposite, governed by surface albedo changes